Relationship between Cefquinome PK/PD Parameters and Emergence of Resistance of Staphylococcus aureus in Rabbit Tissue-Cage Infection Model - Xiong, Mingpeng; Wu, Xun; Ye, Xiaomei; Zhang, Longfei; Zeng, Shuyi; Huang, Zilong; Wu, Yuzhi; Sun, Jian; Ding, Huanzhong (Frontiers in Microbiology, 2016)
In order to explore the relationship between different antibiotic dosing regimens and selective enrichment of resistant strains, tissue-cage infection model was established in rabbits to study relationship between cefquinome pharmacokinetic/pharmacodynamic parameters and the change of susceptibility of Staphylococcus aureus (S. aureus). In this model, above 108 CFU/ mL of S. aureus culture were exposed to cefquinome concentrations below the MIC99 (the minimal concentration that inhibits colony formation by 99% in vitro, 0.3 µg/ mL ), between the MIC99 and the MPC (the mutant prevent concentration in vitro, 1.6 µg/ mL), and above the MPC after intramuscular injection with cefquinome at doses of 4, 8, 16, 32 mg/kg of body weight once daily for 5 days or 4, 8, 16, 24 mg/kg of body weight twice daily for 2.5 days. Samples of tissue-cage fluid were collected from the tissue-cage at 2, 4, 6, 8, 10, 12, 24h after each dosing (one dosing daily) or at 2, 4, 6, 8, 10, 12h (two dosing daily). Cefquinome concentration, susceptibility of S. aureus to cefquinome, and bacterial numbers at the infected site were monitored. The MICs of S. aureus and the fraction of resistant bacteria both increased when cefquinome concentrations fluctuated between the MIC99 and MPC. Resistant bacteria were selected in vivo when %T>MPC was < 58% of administration interval or %T>MIC99 was ≥ 70% of administration interval. These findings demonstrate that low-level cefquinome-resistant S. aureus were selected predominantly when drug concentrations fell inside a concentration window in in vivo model, which was evidenced by pulsed field gel electrophoresis. The selection of resistant bacteria arose from both susceptible bacteria being killed and resistant bacteria re-growth. Keeping drug concentrations above the MPC for ≥ 58% of administration interval provides a strategy to achieve effective antibacterial activity and minimize the emergence of resistance to cefquinome.